CHINA-ARAB ENERGY COOPERATION: CONSTRUCT NEW ENERGY SILK ROAD - Yisen, Zhang (PEOPLE: International Journal of Social Sciences, 2024)
Arab countries are one of the most important energy supply bases in the world and a key area for China's ‘Belt and Road’" initiative(BRI). China and Arab countries have long been committed to enhancing energy cooperation. While the global energy transition is the background of China-Arab energy cooperation, the international situation in the region is still in flux, but there is a good political foundation for China-Arab energy cooperation. These are the basic conditions for China-Arab energy cooperation. Against the backdrop of energy transition and continuous changes in the international situation, China and Arab countries are working together to promote energy cooperation in terms of policy design, mechanism improvement, industry chain layout, human resource support and project implementation, combining the BRI and ‘a Community with a Shared Future for Mankind’, and the ‘China-Arab Community with a Shared Future’ in order to promote the building of a China-Arab community of energy cooperation. China-Arab cooperation in the oil and gas sector continues at a high level, while new energy sources are becoming the highlight of China-Arab energy cooperation, which is the ‘new’. In addition, despite frequent changes in the international situation, China and Arab countries have insisted on promoting a community-based approach to cooperation, which is a ‘new’ way of cooperation compared to the energy strategies of Western countries.